Biodiversity and ecosystem functioning: Have our experiments and indices been underestimating the role of facilitation?. (12th May 2021) - Wright, Alexandra J.; Barry, Kathryn E.; Lortie, Christopher J.; Callaway, Ragan M.
Abstract: After 25 years of biodiversity experiments, it is clear that higher biodiversity (B) plant communities are usually more productive and often have greater ecosystem functioning (EF) than lower diversity communities. However, the mechanisms underlying this positive biodiversity– ecosystem functioning (BEF) relationship are still poorly understood. The vast majority of past work in BEF research has focused on the roles of mathematically partitioned complementarity and selection effects. While these mathematical approaches have provided insights into underlying mechanisms, they have focused strongly on competition and resource partitioning. Importantly, mathematically partitioned complementarity effects include multiple facilitative mechanisms, including dilution of species‐specific pathogens, positive changes in soil nutrient cycling, associational defence and microclimate amelioration. Synthesis . This Special Feature takes an experimental and mechanistic approach to teasing out the facilitative mechanisms that underlie positive BEF relationships. As an example, we demonstrate diversity‐driven changes in microclimate amelioration. Articles in this Special Feature explore photoinhibition, experimental manipulations of microclimate, lidar examinations of plant canopy effects and higher‐order trophic interactions as facilitative mechanisms behind classic BEF processes. We emphasize the need for future BEF experiments to disentangle the facilitative mechanisms that are interlinked with niche complementarity to better understand the fundamental processes by which diversity regulates life on Earth. Abstract : This special feature takes an experimental and mechanistic approach to teasing out the facilitative mechanisms that underlie positive BEF relationships. As an example, we demonstrate diversity‐driven changes in microclimate amelioration. Articles in this special feature explore photoinhibition, experimental manipulations of microclimate, lidar examinations of plant canopy effects, and higher order trophic interactions as facilitative mechanisms behind classic BEF processes. We emphasize the need for future BEF experiments to disentangle the facilitative mechanisms that are interlinked with niche complementarity to better understand the fundamental processes by which diversity regulates life on Earth.